2021
DOI: 10.1002/pmrj.12681
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unplanned transfers among cancer patients at a freestanding acute rehabilitation facility

Abstract: Background: Cancer patients undergoing inpatient rehabilitation often have high risk of complications leading to unplanned transfer to acute care. Prior studies have identified factors associated with these transfers but have been limited to examining factors that pertain to initial admission to rehabilitation and were not conducted in a freestanding inpatient rehabilitation facility.Objective: The study aimed to include these prerehabilitation factors in addition to factors upon initial assessment in rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Therefore, patients with subacute stroke were chosen and analyzed as a control group for patients with brain tumor in this study. Patients with brain tumor were younger than patients with subacute stroke in this study, similar to findings of previous studies [ 20 , 21 ] showing that the mean age was 53.3 years for those diagnosed with a brain tumor and 69.2 years for those diagnosed with a stroke. Proportions of comorbidities such as hypertension, diabetes mellitus (DM), and hyperlipidemia were higher in patients with subacute stroke, consistent with previous study results showing that stroke-related comorbidities were the most common in the order of hypertension, DM, and hyperlipidemia [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, patients with subacute stroke were chosen and analyzed as a control group for patients with brain tumor in this study. Patients with brain tumor were younger than patients with subacute stroke in this study, similar to findings of previous studies [ 20 , 21 ] showing that the mean age was 53.3 years for those diagnosed with a brain tumor and 69.2 years for those diagnosed with a stroke. Proportions of comorbidities such as hypertension, diabetes mellitus (DM), and hyperlipidemia were higher in patients with subacute stroke, consistent with previous study results showing that stroke-related comorbidities were the most common in the order of hypertension, DM, and hyperlipidemia [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Infection has been found to be the most common reason for transfer back to the primary acute care service of cancer acute rehabilitation inpatients in multiple studies. 9,13,14,15,16,17 However, only 2/15 (13.3%) patients in our study returned to the primary acute care service due to infection. One was a wound infection (categorized under neurosurgical complications) and the other was an aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 59%
“…Foley catheters are often present in low functioning patients due to the di culty with transfers and mobility to the bathroom or commode. Previous studies of acute inpatient rehabilitation general cancer populations have also found relationships with lower function and transfer to the primary acute care service including studies by Bhakta et al 13 (lower 6 minute walk test) and Asher et al 10 (lower Motor FIM which includes all FIM items except the last 5 items related to cognition/communication). A similar relationship with lower admission functional level and the likelihood of medical complications and/or transfer to the primary acute care service was found in four stroke acute inpatient rehabilitation studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…41 Hematologic malignancies and stem cell transplant patients have been recognized as among the most medically fragile cancer rehabilitation populations with some of the highest rates of return to the primary acute care service. 42 Transfer rates of 28% for hematologic malignancies, 43 37% for leukemia, 44 38% for lymphoma, 45 and 26% for multiple myeloma 46 have been reported.…”
Section: Medical Complications During Acute Inpatient Rehabilitationmentioning
confidence: 99%